Molecular Phylogeny of Floral Visitors of Sesame (Sesamum indicum) - Sarkar, Rupanwita (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Evolutionary analyses were conducted in NCBI blast followed by Mega 11. Finally, a phylogenetic tree was constructed which can indicate at its taxonomic level. The study carried out on the pollinator fauna, reveal that pollinators visiting sesame plants. These three insects are separate that is not related with each other but a comparative account has been done through DNA sequencing method and bioinformatics study. Hymenopterans are the major pollinators visiting sesame flowers. To date there was no report of the molecular phylogeny of these particular genera.